Wine, terroir and utopia - Dutton, Jacqueline; Howland, Peter, 1961- (Abingdon, Oxon ; New York, NY : Routledge, 2019)
"Wine, Terroir and Utopia critically explores these three concepts from multi-disciplinary and intersecting perspectives, focusing on the ways in which they collide to make new worlds, new wines, new places and new peoples. Wine, terroir and utopia are all rooted in natural, spatial and temporal realities, yet all are unable to exist without purposeful human intervention. This edited volume highlights the theoretical and analytical lens of diverse scholars, who critically discuss a dazzling array of intersecting realities and imaginaries--economic, political, cultural, social and geological--and in doing this challenge many of our deeply-held responses to utopia. Drawing on an impressive range of international examples from South Africa to Bordeaux to New Zealand, the chapters adopt a range of theoretical and methodological approaches. This volume will be of great interest to upper level students, researchers and academics in the fields of Sociology, Geography, Tourism, Hospitality, Wine Studies and Cultural Studies. It will also greatly appeal to practitioners and enthusiasts in the worlds of wine production, consumption and marketing"--
Introduction: Making new worlds : the utopian potentials of wine and terroir -- The four pillars of utopian wine : terroir, viticulture, degustation, and cellars -- To wash away a British stain : class, trans-imperialism and Australian wine imaginary -- Liberty and order : wine and the South Australian project -- Burgundy's climats and the utopian wine heritage landscape -- Inventing tradition and terroir : the case of Champagne in the late nineteenth century -- Terroir wines in Champagne : between ideology and utopia -- Ecotopian mobilities : terroir driven tourism and migration in British Columbia, Canada -- Certified utopia : ethical branding and the wine industry of South Africa -- The commercial basis of terroir utopias in Calabria -- Ideals for sustainability in the Australian wine industry : authenticity and identity -- Utopia regained : nature and the taste of terroir -- Utopia is just up the road and toward the past : young Australian winemakers return to ancient methods -- Deep terroir as utopia : explorations of place and country in Southeastern Australia -- Plain-sight utopia : boutique winemakers, urbane vineyards and terroir-torial moorings.
OCLC-licensed vendor bibliographic record.
Keywords: Wine and wine making -- Social aspects; Terroir; Utopias; Wine tourism; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism